Leveraging social media activities for purchase intention: Exploring brand loyalty and perceived quality as mediation - Olfebri Olfebri; Sarovah Widiawati; Rizki Amelia; Tiara Putri Meitrisya (Green Publisher, 2025)
In the airline industry, this study analyzes how social media marketing activities affect brand equity (perceived quality and brand loyalty) as well as consumers' intentions to buy. A questionnaire was distributed to 125 Instagram users who were airline passengers for obtaining quantitative data. The information were handled and investigated utilizing SEM-PLS 4.1.0.6. According to the study, social mdia marketing increases brand loyalty and brand quality perception. Purchase intentions are also significantly influenced by loyalty and perceived quality. Additionally, the study indicates that all moderating effect variables, such as brand loyalty and perceived quality, are involved in mediating the impact of social media marketing on purchase intentions. The findings are expected to be relevant for social media activity strategies, particularly for airlines in Indonesia.